2018
DOI: 10.1111/1365-2478.12631
|View full text |Cite
|
Sign up to set email alerts
|

Directional‐oriented wavefield imaging: a new wave‐based subsurface illumination imaging condition for reverse time migration

Abstract: The key objective of an imaging algorithm is to produce accurate and high‐resolution images of the subsurface geology. However, significant wavefield distortions occur due to wave propagation through complex structures and irregular acquisition geometries causing uneven wavefield illumination at the target. Therefore, conventional imaging conditions are unable to correctly compensate for variable illumination effects. We propose a generalised wave‐based imaging condition, which incorporates a weighting functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As for the development of conjugate gradient algorithm and illumination preprocessing, Liu et al 15 performed time-domain full waveform inversion for eight versions of the CG method, and numerical experiments showed that the PRP conjugate gradient (PRPCG) method is more efficient. Kim et al 16 proposed direction-oriented wavefield imaging, which compensates for possible illumination effects during acquisition and can produce high-fidelity depth profiles and correct imaging of complex wavepaths. Yu et al 17 developed a 3D nonlinear conjugate gradient traveltime inversion method using the PRP conjugate gradient method for solving constrained damping least squares problems, and model tests showed that the method can substantially improve the inversion resolution.…”
Section: Introductionmentioning
confidence: 99%
“…As for the development of conjugate gradient algorithm and illumination preprocessing, Liu et al 15 performed time-domain full waveform inversion for eight versions of the CG method, and numerical experiments showed that the PRP conjugate gradient (PRPCG) method is more efficient. Kim et al 16 proposed direction-oriented wavefield imaging, which compensates for possible illumination effects during acquisition and can produce high-fidelity depth profiles and correct imaging of complex wavepaths. Yu et al 17 developed a 3D nonlinear conjugate gradient traveltime inversion method using the PRP conjugate gradient method for solving constrained damping least squares problems, and model tests showed that the method can substantially improve the inversion resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Salt basins, like the Gulf of Mexico and Angola, are one of most prospective places for oil and gas exploration (Leveille et al ., 2011). Seismic illumination is one key issue for subsurface imaging (Kim et al ., 2018) and reservoir characterization (Zambrini et al ., 2020), but the subsalt targets usually suffer from the problem of poor illumination (Liu et al ., 2011; Um et al ., 2014). The oil and gas industry has made great strides over the past two decades, but some fundamental challenges – such as imaging of poorly illuminated subsalt structures and complex salt interpretation – have not been entirely overcome (Etgen et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%